Five Pistacia species (P. vera, P. atlantica, P. terebinthus, P. khinjuk, and P. lentiscus): A Review of Their Traditional Uses, Phytochemistry, and Pharmacology - Mahbubeh Bozorgi; Zahra Memariani; Masumeh Mobli; Mohammad Hossein Salehi Surmaghi; Mohammad Reza Shams-Ardekani; Roja Rahimi (The Scientific World Journal)
Pistacia, a genus of flowering plants from the family Anacardiaceae, contains about twenty species, among them five are more popular including P. vera, P. atlantica, P. terebinthus, P. khinjuk, and P. lentiscus. Different parts of these species have been used in traditional medicine for various purposes like tonic, aphrodisiac, antiseptic, antihypertensive and management of dental, gastrointestinal, liver, urinary tract, and respiratory tract disorders. Scientific findings also revealed the wide pharmacological activities from various parts of these species, such as antioxidant, antimicrobial, antiviral, anticholinesterase, anti-inflammatory, antinociceptive, antidiabetic, antitumor, antihyperlipidemic, antiatherosclerotic, and hepatoprotective activities and also their beneficial effects in gastrointestinal disorders. Various types of phytochemical constituents like terpenoids, phenolic compounds, fatty acids, and sterols have also been isolated and identified from different parts of Pistacia species. The present review summarizes comprehensive information concerning ethnomedicinal uses, phytochemistry, and pharmacological activities of the five mentioned Pistacia species.